Implementation Of Quick Response (QR) Code In Cloud Manufacturing (CM) Framework - Jamalulil, Nur Halimah (2016)
Cloud computing, information and communication technologies (ICT), and Internet of Things (IoT) have evolved into key assets in a manufacturing firm, particularly as a medium in transmitting information to specific parties. Cloud manufacturing (CM), which has espoused both technologies, has rose to prominence in terms of transforming the existing manufacturing practice in firms into a service-focused, customer-oriented, demand-powered, and extremely collaborative process. Thus, the deployment of CM in a shipbuilding firm aims to address multiple problems that had cropped up. The concerns faced by the shipbuilding firm are: (i) ever-evolving demands and expectations from consumers, (ii) insufficient inter-dependent mediums of communication, and (iii) wastage of material in manufacturing. To address these issues, this study intends to recommend a new framework which can envisage the CM assimilated with the work processes which are to be executed in the shipbuilding firm. The entire manufacturing process in the X boat model is examined for formulating the framework. For the framework to be worked out, the present workflow and customs of the shipbuilding firm for the creation of the X boat model are determined and structured. This helps identify the issues with the present framework as well as the crucial departments which require improvement. These departments are as follows: (i) production planning, (ii) engineering & design, and (iii) store. Enhancements are carried out on the identified issues of these departments for formulating the new framework. As the majority of the arising issues pertain to the communication system in transmitting information within departments, the CM concept is deployed across the cloud data storage. This storage is the place where information is stowed and then accessed through the Quick Respond (QR) code system organised for the firm. The assimilation of the QR code system and cloud data storage is envisaged in the recommended framework. This framework is then substantiated by implementation verification and is corroborated through the face validity method. Following the substantiation and corroboration of the new proposed framework, the execution of the QR code system which focuses on the CM concept and the feasibility of the system have been elucidated in detail. This, in turn, is able to enhance the production and communication workflow in the shipbuilding organisation.